2023
DOI: 10.7759/cureus.33241
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Primary Care: A Scoping Review

Abstract: The COVID-19 pandemic had a severe impact on various aspects of everyday life, including healthcare provision. The aim of the scoping review was to collate, summarize, and discuss this literature, in light of the impact COVID-19 had on Primary care. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) four-stage process framework for reporting was followed. A total of 31 studies were included in this review. Based upon our review we found COVID-19 pandemic on Primary Care, has made signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The pragmatic responses to COVID-19 were largely driven within the medical com- Whilst some benefits from better data sharing and better IMS have been stepped back from, others have persisted. For example, the changes included a shift to remote consultation which has persisted [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The pragmatic responses to COVID-19 were largely driven within the medical com- Whilst some benefits from better data sharing and better IMS have been stepped back from, others have persisted. For example, the changes included a shift to remote consultation which has persisted [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that telemedicine is here to stay (45). The potential negative consequences and risks are clearly recognised such as widening the gap between the advantaged and the disadvantaged (46), and the doubts about the quality of such consultations (47). However, the wider implementation has also shown good examples, where for instance, telemedicine helped the deprived gain access to care (48).…”
Section: Discussionmentioning
confidence: 99%
“…58 Rules related to social distancing were still in place during fieldwork, and most medical practices in the United Kingdom significantly changed the way they operated during COVID. [59][60][61] Research has shown that among the most affected by those changes, in terms of health outcomes, were those with long-term conditions and multimorbidity. 62 Patients' perceptions and experiences were possibly influenced by those changes.…”
Section: Strengths and Limitationsmentioning
confidence: 99%